1970
DOI: 10.1177/002383097001300402
|View full text |Cite
|
Sign up to set email alerts
|

General Language Deficits in Children With Articulation Problems

Abstract: Sixteen 7 year-old children with normal articulation, and sixteen 7 year-old children with defective articulation were compared as to their performance on series of language tests designed to assess the child's knowledge of form class, sentence structure, and phonological composition in English. Results showed that children in the defective articulation group gave significantly fewer paradigmatic responses in a word-association test, were less able to discriminate possible from impossible phoneme sequences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1973
1973
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…In testing children's knowledge of phonological and syntactic rules, Whitacre, Luper and Pollio (1970) observed that children with articulatory deficits produced fewer paradigmatic responses in the word association test, were less able to discriminate possible from impossible phoneme sequences in English, and repeated fewer sentences correctly than the control children. The authors suggested that assessment of children with articulatory deficits include the individual's ability to utilize grammatical rules of language.…”
Section: Intelligibility and Articulatory Deficitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In testing children's knowledge of phonological and syntactic rules, Whitacre, Luper and Pollio (1970) observed that children with articulatory deficits produced fewer paradigmatic responses in the word association test, were less able to discriminate possible from impossible phoneme sequences in English, and repeated fewer sentences correctly than the control children. The authors suggested that assessment of children with articulatory deficits include the individual's ability to utilize grammatical rules of language.…”
Section: Intelligibility and Articulatory Deficitsmentioning
confidence: 99%
“…Further consideration was given to the relationship between severe articulatory defects and delayed syntax development in children (Shriner, Holloway & Daniloff, 1969;Whitacre, Luper & Pollio, 1970;Panagos, 1974). Researchers concluded that severe articulatory deficits constituted linguistic disorders of the phonological type (Compton, 1970;Ingram, 1976).…”
Section: Intelligibility and Articulatory Deficitsmentioning
confidence: 99%
“…In the case of children with deviant speech, the amount of filtering is greater than for the normal child. They seem to be particularly affected by transformational complexity and limitations on short-term memory performance (Jackson and Sommers, to appear;Menyuk, 1969 ;Whitacre et al, 1970). Omission errors predominate, although essential semantic properties are left intact (Menyuk, 1969).The purpose of this study was to examine the sentence repetitions of a group of children with normal decoding abilities, but with severe deficits in speech-motor performance as reflected in their largely unintelligible speech as perceived by clinicians and others.…”
mentioning
confidence: 99%
“…In the case of children with deviant speech, the amount of filtering is greater than for the normal child. They seem to be particularly affected by transformational complexity and limitations on short-term memory performance (Jackson and Sommers, to appear;Menyuk, 1969 ;Whitacre et al, 1970). Omission errors predominate, although essential semantic properties are left intact (Menyuk, 1969).…”
mentioning
confidence: 99%
See 1 more Smart Citation